The Model of Nonstationary Rotor Magnetic Field Observer in the Induction Motor - Burkov, Alexander; Krasilnikyants, Evgenii; Smirnov, Alexander (Electrical, Control and Communication Engineering, 2011)
This article is devoted to the questions, associated with observer construction for monitoring the values of rotor magnetic vector magnitude and angular deflection of induction motor oriented on bidimensional convolution on temporal and spatial actual parameters. The interrelation of induction motor breakdown torque and rotor characteristic time and transportation lag is shown. The system of rotor running stream observer on the basis of gage rotor position and stator current is put forward.